Problems of communication in developing countries - "Sondhi, Krishan" (New Delhi, 1981)
The relevance of Operational Research (OR) in developing countries has increasingly engaged the attention of operational researchers in both the industrialised and less developed countries over the last 50 years. With this, there has been a considerable amount of interest in the potential for using OR in developing countries. One sign of this is the emergence of a number of initiatives to promote OR in developing countries and the number of new societies for OR that have emerged from the developing world. This paper is an attempt at providing an overall picture of the state of OR in the developing countries. In particular, it will look at the coverage in terms of countries and methods. It will also highlight the contribution OR is making towards the theme of poverty, the reduction of which is regarded as the key focus of development policy interventions as reflected in the Millennium Development Goals (MDGs).
Keywords: Communication